Antimicrobial activity of chitosan and carboxymethyl chitosan from diferent types and sources of chitosan - Tantala,J. (Chiriotti Editori, 2015)
The aim of this study was to determine the antimicrobial activity of chitosans and carboxymethyl chitosan (CMCH) from two molecular sizes (polymer and oligomer) and three sources (shrimp, crab and squid). The CMCH were synthesized via carboxymethylation method with monochloroacetic acid in isopropyl alcohol under alkaline condition. The antibacterial activity of chitosan and CMCH were examined against sixteen of food borne pathogenic bacteria and two strains of lactic acid bacteria (LAB). The minimum inhibitory concentration (MIC) of chitosans and CMCH were examined by agar dilution method and the minimum bactericidal concentration (MBC) values were determined by broth dilution method. The results showed that all types of chitosans were generally more effective antibacterial than CMCH. The MIC of chitosans ranged from 0.008-0.15% and MBC ranged from 0.01-0.18%. LAB was the most sensitive strain to the chitosan groups (MIC = 0.008%, MBC = 0.01%). In contrast, all CMCH groups had no effect against foodborne pathogenic bacteria (MIC and MBC were higher than 1%) except for LAB which was inhibited by oligomeric CMCH, in which those of the MIC and MBC values were less than chitosan oligomer at 45-56.25 times and 25 times, respectively (MIC and MBC of chitosan crab oligomer = 0.008-0.01% and 0.02%, respectively). These observations suggested that the antibacterial activity of chitosan and CMCH depends on the chitosan sources, molecular size and the target microorganism. Therefore, application of chitosan and CMCH must be chosen selectively in order to control the target foodborne pathogens.